The moose nose bot fly Cephenemyia ulrichii Brauer (Diptera: Oestridae) reported in Norway for the first time - Nilssen, Arne C.; Haugerud, Rolf E. (Rangifer, 1994)
Our conclusion is that C. ulrichii has reached the northeastern part of Norway (Pasvik). A further expansion of this parasite may be expected in Norway as well as in southern Sweden. This study shows that moose can be sampled for C. ulrichii with the described technique in the hunting season when the larvae are in their first instar.